Understanding the metabolic and health effects of low-calorie sweeteners: methodological considerations and implications for future research - Sylvetsky, Allison C. (Rev Endocr Metab Disord, 2016)
Consumption of foods, beverages, and packets containing low-calorie sweeteners (LCS) has increased markedly across gender, age, race/ethnicity, weight status, and socioeconomic subgroups. However, well-controlled intervention studies rigorously evaluating the health effects of LCS in humans are limited. One of the key questions is whether LCS are indeed a beneficial strategy for weight management and prevention of obesity. The current review discusses several methodological considerations in the design and interpretation of these studies. Specifically, we focus on the selection of study participants, inclusion of an appropriate control, importance of considering habitual LCS exposure, selection of specific LCS, dose and route of LCS administration, choice of study outcomes, and the context and generalizability of the study findings. These critical considerations will guide the design of future studies and thus assist in understanding the health effects of LCS.